Pemberdayaan Masyarakat melalui Pengelolaan Sampah dan Minyak Jelantah menjadi Nilai Ekonomis di Desa Tirtayasa Serang - Ubay Haki; Ika Novarina; Arini Arini; Anton Wijaya (Batara Wisnu : Indonesian Journal of Community Services, 2022)
The Tirtayasa Village Government has a plan to develop a tourist village. The idea of developing a tourist village came from the association of village officials who are members of the Tirtayasa village rose which has a mission of environmental conservation and economic development of tirtayasa villagers. Awareness to preserve the natural potential of the village as a tourist attraction is carried out by means of 1) Hygiene awareness movement 2) Cooperation with the Environmental Agency (DLH) of Serang Regency 3) Cooperation with the Digital Waste Bank 4) Citizen education about the 3R movement (Reduce, Reuse, Recycle) 5) Management of the economic potential of domestic waste in community service programs. The Student Work Lecture Program (KKM) related to community service in Tirtayasa village can help overcome environmental problems related to accumulated domestic waste, increase awareness of clean and healthy living behaviors (PHBS) and provide citizen engagement related to environmental awareness through the economic value of waste in improving family welfare. Keywords: 3R, community development, waste, community welfare